Meningkatkan Mutu Pendidikan Melalui Kegiatan Bimbingan Belajar Gratis di Desa Banua Huta Kecamatan Sigumpar Kabupaten Toba, Sumatra Utara - Simanjuntak, Harlen; Simanjuntak, Lasmi Enjelina; Tambunan, Christy Adventina; Aruan, Alisa Falestina; Pasaribu, Ibram; Siagian, Ebun Romauli (UKInstitute, 2022)
This community service activity (PkM) aims to improve the quality of people's education through free tutoring after school at SDN177674 Banua Futa, Shigunpa District, Toba Regency. Tutoring activities were carried out at SDN177674 Banua Futa, Shigunpa District, Toba Regency. This activity will last for a month from February 2, 2022 to February 28, 2022. Teaching hours are from 15.00 WIB to 17.00 WIB from Monday to Thursday. The teacher instructs students to complete school assignments (PR) and teaches students about material that has not been understood while studying at school. The material provided covers all subjects and all grade levels. This guidance stage includes preparation, implementation, assessment, and reporting of activities. The result of this tutoring activity is the satisfaction of parents/guardians towards improving children's academic achievement after participating in this tutoring activity. This is because after joining a tutor, students are enthusiastic about doing their homework (PR) well and don't give up doing homework because of the teacher. You can also review the material provided by the tutor in the afternoon after school to further improve your students' understanding of the material at school